Sevoflurane Inhibits Traumatic Brain Injury-Induced Neuron Apoptosis via EZH2-Downregulated KLF4/p38 Axis - Wang, Zhongyu; Li, Juan; Wang, Anqi; Wang, Zhaoyang; Wang, Junmin; Yuan, Jingjing; Wei, Xin; Xing, Fei; Zhang, Wei; Xing, Na (Frontiers in Cell and Developmental Biology, 2021)
Traumatic brain injury (TBI) is characterized by physical damage to the brain tissues, ensuing transitory or permanent neurological dysfunction featured with neuronal loss and subsequent brain damage. Sevoflurane, a widely-used halogenated anesthetic in clinical settings, has been reported to alleviate neuron apoptosis in TBI. Nevertheless, the underlying mechanism behind this alleviation remains unknown, and thus was the focus of the current study. First, Feeney models were established to induce TBI in rats. Subsequently, evaluation of the modified neurological severity scores, measurement of brain water content, Nissl staining, and TUNEL assay were employed to investigate the neuroprotective effects of sevoflurane. Immunofluorescence and Western blot analysis were further applied to detect the expression patterns of apoptosis-related proteins as well as the activation of the p38-mitogen-activated protein kinase (MAPK) signaling pathway within the lesioned cortex. Additionally, a stretch injury model comprising cultured neurons was established, followed by neuron-specific enolase staining and Sholl analysis. Mechanistic analyses were performed using dual-luciferase reporter gene and chromatin immunoprecipitation assays. The results demonstrated sevoflurane treatment brought about a decrease blood-brain barrier permeability, brain water content, brain injury and neuron apoptosis, to improve neurological function. The neuroprotective action of sevoflurane could be attenuated by inactivation of the p38-MAPK signaling pathway. Mechanistically, sevoflurane exerted an inhibitory effect on neuron apoptosis by up-regulating enhancer of zeste homolog 2 (EZH2), which targeted krüppel-like factor 4 (KLF4) and inhibited KLF4 transcription. Collectively, our findings indicate that sevoflurane suppresses neuron apoptosis induced by TBI through activation of the p38-MAPK signaling pathway via the EZH2/KLF4 axis, providing a novel mechanistic explanation for neuroprotection of sevoflurane in TBI.